PENERAPAN METODE RAPID APPLICATION DEVELOPMENT DALAM IMPLEMENTASI APLIKASI PERGUDANGAN BERBASIS WEBSITE STUDI KASUS UMKM ABIZAR JAYA - Wildan Maulid Nurhadi, Muhamad; Sidiq, Maulana; Dwicahya Supriatman, Rian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Efficient warehouse management is crucial for the success of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. However, MSMEs often face challenges in implementing optimal warehouse management due to limited resources and a lack of awareness regarding the importance of proper inventory management. This study aims to develop a web-based warehouse application using the Rapid Application Development (RAD) method as a solution to address warehouse management issues at MSME Abizar Jaya in Tasikmalaya. The research involved identifying problems through observation, interviews, and literature reviews, followed by system development in three phases: requirements planning, system design, and system implementation. The findings indicate that the developed warehouse application successfully enhances operational efficiency and reduces errors in inventory management. The web-based system allows MSME Abizar Jaya to monitor inventory in real-time and make more informed decisions regarding purchasing, production, and marketing strategies. Thus, this research offers practical contributions to MSMEs in optimizing warehouse management and supports better decision-making through clear visibility of inventory data.